The Effect of Sales Growth and Dar on the Profitability of Infrastructure Sector Companies Listed on the IDX In 2020-2022 - MARELLA, Tyas Nindya; PUTRI, Andin Cipta; AMELIA, Zahwa Putri (PT Keberlanjutan Strategis Indonesia, 2023)
Infrastructure is the most important thing in the progress of a country. Several countries in the world have been able to develop forward thanks to a strong infrastructure foundation supported by good synergies between government companies and the private sector. Infrastructure development is an important matter in the process of growing a nation in the economic, educational, social, cultural, agricultural, and other sectors. This study aims to determine the effect of sales growth and DAR (Debt to Assets Ratio) on company profitability (Return on Asset). This research was conducted on infrastructure sector companies listed on the Indonesia Stock Exchange for 2020-2022. The population in this study are all infrastructure companies listed on the Indonesia Stock Exchange (IDX) for 2020-2022, totaling 37 companies. The sample selection used a purposive sampling technique with several predetermined criteria, so the number of samples was 11 companies. The research data is secondary data obtained from the Indonesian Stock Exchange (IDX) 2020-2022. Data were analyzed using panel data regression with the help of Stata software version 14 to determine the significant level of each independent variable regression coefficient to the dependent. The results showed that sales growth and DAR (Debt to Asset Ratio) simultaneously had a positive effect on company profitability (Return on Asset). Sales growth has no effect on profitability, and DAR (Debt to Asset Ratio) has a negative effect on company profitability (Return on Asset).